Sustainable Strategy for Community-Based Drinking Water Supply (PAMSIMAS) Post Program In Rural Indonesia - Kurniatin, Putri Rut Elok; Maksum, Irfan Ridwan (Journal of Governance and Public Policy, 2022)
PAMSIMAS acted as a platform for basic services for the community, therefore post-program sustainability in rural areas would greatly affect its basic services. Currently, the problems at hand are that PAMSIMAS villages, which have received assistance for the construction of facilities and infrastructures, are having troubles in maintaining the management and a number of them are on the verge of abandonment due to limited resources, and the community and village government are not equipped with enough resources to follow up after the program. This study aims to analyze the sustainable strategy after the community-based rural water supply program which ended in 2021 using qualitative methods. Data collection came from secondary data from literature reviews from journals and primary data by interviewing informants. The findings and results of this study highlight that adjusting the community institutions and village government in their place, ownership of assets after the PAMSIMAS program, mainstreaming basic drinking water services in village planning and budgeting, and increasing public awareness of the environment are strategic efforts as well as policies to support sustainable fulfillment of needs. drinking water after the end of the program.